Joep Leerssen’s imagology and Yuri Lotman’s semiotic ideas - Khalipov, Victor (Vilnius University Open Series, 2024)
Having emerged as an independent branch of literary studies, today, imagology is represented by various schools. Its most prominent representative, Joep Leerssen, has developed a holistic version of the imagological theory, which, in many respects, correlates with constructivist approaches to understanding nationalism. The main categories of imagology as interpreted by this school are ethnic stereotype, ethnotype, category of the imaginary, non-falsifiability, imagotypes, imaginary discourse, auto-image, hetero-image, context, common places, imagemes, and the representativeness trap. From the point of view of semiology, ethnic stereotypes, which are studied by imagology, are the signs by means of which their bearer interprets for himself the sphere of interaction between people, in which they act as representatives of certain nations. Thus, the imagosphere can be interpreted as part of the semeosphere, distinguished from it only by problem-thematic rather than by structural-functional features. Accordingly, many of Yuri Lotman’s semiotic ideas can potentially be productive for research in the field of imagology. Imagologists and semiologists analyze the same works of literature and formulate different conclusions largely because they use different types of the scientific discourse in the categories of which they conduct their research. However, in essence, these conclusions are often not so different, at least not mutually exclusive.